2020
DOI: 10.3390/ijerph17249176
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Age Differences in Loneliness: Evidence for People without and with Disabilities

Abstract: This study examines the relationships between loneliness, gender, and age for people without and with disabilities (moderate versus severe) in Germany. Using data taken from the German Socio-Economic Panel (SOEP) for the years 2013 and 2017 and using the UCLA (University of California, Los Angeles) Loneliness Scale, in general we found that males report lower loneliness scores as compared to those for females. Furthermore, we found a strong association between loneliness and the individual’s age, but with diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
34
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 84 publications
7
34
1
1
Order By: Relevance
“…Conversely, only one study identified positive linear regression coefficients ( Luhmann and Hawkley, 2016 ). For both positive and negative linear regression coefficients the magnitude of the relationship between loneliness and paid work was greater in full-time than part-time employment ( Luhmann and Hawkley, 2016 ; Pagan, 2020 ). Five linear regressions presented negative coefficients but did not achieve statistical significance, which was also the case in causal analysis ( Buecker et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Conversely, only one study identified positive linear regression coefficients ( Luhmann and Hawkley, 2016 ). For both positive and negative linear regression coefficients the magnitude of the relationship between loneliness and paid work was greater in full-time than part-time employment ( Luhmann and Hawkley, 2016 ; Pagan, 2020 ). Five linear regressions presented negative coefficients but did not achieve statistical significance, which was also the case in causal analysis ( Buecker et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The remaining studies (10/34) reported descriptive statistics or correlations for this relationship and used regression for analysis elsewhere. Of the longitudinal studies included, two did not seek to understand directionality ( Kalil et al, 2010 ; Pagan, 2020 ), three considered the causal impact of employment status on loneliness ( Bu et al, 2020a ; Buecker et al, 2020 ; von Soest et al, 2018 ) and two the reverse of loneliness on employment outcomes ( Morris, 2019 ; von Soest et al, 2020 ). Further details of study characteristics, data collection and analysis ordered by date of publication can be found in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations